Primary Prevention of COVID 19 - Preksha Luthra (Indian Journal of Forensic Medicine & Toxicology, 2021)
Coronavirus disease - 19 is caused by a newly discovered virus called coronavirus. Coronavirus is a spherical ,enveloped particle with a single stranded RNA which causes acute mild respiratory illness. The transmissionis via airborne droplets. It multiplies in the nasal mucosa causing cell damage and inflammation. COVID19 has been increasing exponentially as it spreads very fast and in a country like India with a population of135 crore it is difficult to curtail the spread of the virus. The steps taken to control this spread such as socialdistancing, nation-wide lockdown were important to restrict the geographical spread of coronavirus. Thevirus is transmitted by droplets which can travel in air when an infected person or carrier coughs or sneezes.Therefore, primary preventive measures like practicing hygiene with soap and water for at least 60 secondsor using alcohol-based hand rub, social distancing and lockdown were implemented. This article covers themethod of hand washing, steps of hand washing and gives information about the do’s and don’ts of alcoholbased hand rubs. It also covers the importance of social distancing and lockdown with the social distancingmethods adopted in India.